Aspiration Pneumonia and oral health: a critical review of literature - Nayara Perpétuo Gonçalves do Nascimento; Patricia Furtado Gonçalves; Dhelfeson Willya Douglas-; Olga Dumont Flecha (Associação Brasileira de Odontologia, 2018)
Objective: to identify evidences in the scientific literature if mechanical or chemical oral hygiene can prevent aspiration pneumonia in hospitalized patients. Material and Methods: it were included clinical studies indexed in Pubmed, Lilacs and Scielo databases from 2008 to 2017, following pre-determined inclusion and exclusion criteria. Results: twelve studies met the inclusion criteria and were reviewed. According to the quality of the evidence, three studies were evaluated as I, six as II and three as III. Regarding the treatment used, clinical researches investigating the effectiveness of different antimicrobial solutions for oral hygiene in order to reduce aspiration pneumonia in hospitalized patients. Different chlorhexidine concentrations (0.05%, 0.1%, 0.12%, 0.2%, 2%) were used, as well as other substances for mouthwash. Conclusion: the lack of high quality studies undermines the confidence on the effectiveness of antimicrobial solutions regarding the reduction of aspiration pneumonia. However, those studies with good methodology suggested the reduction of pneumonia by oral hygiene.